PENDIDIKAN DAN PENGETAHUAN HIDUP BERSIH DAN SEHAT DALAM PERSPEKTIF ISLAM - Mashadi, Imron (Jurnal Ilmiah Pendidikan dan Keislaman, 2022)
Thaharah has a general understanding of lifting barriers (dirt) arising from hadas and unclean that includes the body, clothing, places, and objects carried on the body. Thaharah is the key child and the legal condition of prayer. The law of thaharah is obligatory upon every man and woman’s face. The most important requirement to perform thaharah is Muslim and having puberty. The means used to perform thaharah are holy water, soil, dust, and other objects that are allowed. Water is used for bathing and ablution, dust and soil are used for beryamum if no water is found, while other objects such as stone, paper, and tissues can be used to perform istinja’. Thaharah has the main function of getting used to clean and healthy living as ordered by religion. Thaharah is also a means to communicate with Allah Swt. The benefits of thaharah in daily life are cleaning the body, clothing, and place from hadas and unclean when about to perform worship. "Whoever ablutes and washes his ablution, sins will come out of his body, to the extent that he will come out from under his nails." (HR. Muslims in the Book of at-Thaharah).